High vs Low Context Communication: Analyzing X Reactions to Gus Miftah - Carissa Margaret Sijabat; Nurazizah Yova Ekaputri; Nakhwa Nabilla Atmaja; Sirait, Lenni Herawati; Dian Marisha Putri (FKIP, Universitas Palangka Raya, 2025)
This study analyzes social media comments related to a controversial incident involving Gus Miftah and a street vendor, using Edward T. Hall's theory of High- and Low-Context Communication. The goal is to identify the degree of context in each comment and explore how cultural and social values shape online discourse. A qualitative content analysis was conducted on 9 user-generated comments from a social media platform. The comments were categorized as either High-Context or Low-Context based on the use of cultural references, implicit meanings, and the need for shared cultural knowledge to understand the message. The analysis found that 5 out of 9 comments (55%) were Ligh-Context, while 4 comments (45%) were How-Context. High-context comments often utilized religious symbolism, cultural idioms, and implicit moral critiques, reflecting Indonesia’s deeply rooted religious and moral values. In contrast, low-context comments relied on direct language, explicit criticism, and factual storytelling, making them universally understandable across cultures. The study highlights how local cultural norms, religious values, and moral expectations influence the nature of public discourse online. This approach demonstrates Hall's framework's relevance in cross-cultural communication studies while also providing insights into how Indonesian social media users engage in moral and religious criticism. This analysis can be used as a basis for future research on the intersection of culture, religion, and digital discourse.